Type of Research History: international Evidence - Mery Genoveva; Miraval Tarazona (Al-Qanṭara, 2022)
Abstract The term history is derived from the Greek word istoria‘which means enquiry, research, exploration information or learning. History is an enquiry into human events or learning based on ascertained facts. In a restricted sense, history is nothing but the recorded past based on research. In this sense, history can be used to stand either for a well-known genus of researches and writings which usually take the form of historical books. History is a meaningful record of human achievement. It is not just dates and events but an unique account of relativity between time period, people, places, and events. The study of history has both a practical and educational value. It help us to develop an active enquiring mind, promotes the use of critical skills in the handling and evaluation of various types of source material and assists in the presentation of written work.